1999
DOI: 10.1021/ja9842565
|View full text |Cite
|
Sign up to set email alerts
|

Wild-Type RNA MicrohelixAla and 3:70 Variants:  Molecular Dynamics Analysis of Local Helical Structure and Tightly Bound Water

Abstract: Molecular dynamics simulations of RNA microhelix Ala indicate that G:U and other 3:70 purine: pyrimidine wobble pairs induce local deviations from A-form geometry in their respective microhelices; the helix is underwound at the base-pair step above and overwound at the base-pair step below, in each case by about 7-9°compared to canonical A-form RNA. On the basis of analysis of average water densities and residence lifetimes, the wild-type microhelix strongly binds a water molecule in the minor groove of the 3:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
52
0

Year Published

1999
1999
2014
2014

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 35 publications
(59 citation statements)
references
References 52 publications
7
52
0
Order By: Relevance
“…Meaningful interpretation of MD simulations requires that each trajectory's stability be determined+ To this end, various parameters were examined to assess convergence+ The root-mean-square deviation (RMSD) from the average structure was calculated for the wild-type microhelix Ala simulation and each of the 2:71 variant simulations over a 2-ns production run time (Fig+ 5)+ Analyses of helical parameters were also examined, including local twist, base-pair inclination, and x-displacement from the global helical axis+ Appreciable fluctuations from a constant value were not observed in the RMSDs or in the helical parameters (data not shown)+ Thus, all trajectories in this study were established as reliable for interpretation+ All helices exhibited A-form geometries with the exception of local twist deviations around the G3:U70 wobble base pair+ Such geometries are consistent with prior NMR, X-ray, and MD simulation studies on the wild-type microhelix and related analogs (Ramos & Varani, 1997;Vogtherr et al+, 1998;Mueller et al+, 1999;Nagan et al+, 1999)+ Analysis of hydration indicated a water molecule to be tightly bound at the 3:70 position in every case examined here, consistent with prior experiments and simulations (Mueller et al+, 1999;Nagan et al+, 1999) for wild-type microhelix Ala + Along with structural properties, we also examined the relationship between base-pair substitution and RNA electrostatic properties+ The electrostatic potential (ESP) computed by solving the linearized PB equation is expressed as the free energy of interaction between the RNA and a unit positive charge+ The calculation is performed considering two different dielectric regions (solute and solvent) defined by the solvent-accessible surface+ This type of calculation can provide insights into how a cation, a positively charged side chain, or a protein with a positive electrostatic potential may interact with the RNA+ Such sites will also interact strongly with hydrogen-bond donating groups, including water+ PB calculations are routinely used to describe proteinsmall molecule (Ullmann et al+, 2000) and protein-DNA interactions (Misra et al+, 1994), and recently, Chin and coworkers have used PB methods to describe specific RNA electrostatics (Chin et al+, 2000)+ Van der Waals components can be further added to the electrostatic component in such a way that steric effects, derived from the actual size of atoms involved in the interaction, are also taken into account+ The sum of these two terms defines the molecular interaction potential (MIP), as originally described in the context of quantum mechanical systems by Orozco and Luque and later extended to classical systems (Orozco & Luque, 1993)+ MIP isopotential contours at Ϫ5+5 kcal/mol for various microhelices are shown in Figure 6+ All microhelices are shown from the major groove side+ The isopotential contour around the wild-type microhelix Ala indicates that there is a large region of negative interaction potential throughout the major groove, beginning at the 5:68 base pair and extending up the helix roughly to the 2:71 base pair+ Notwithstanding structural similarities between all microhelices studied, a striking difference in interaction potentials was observed with respect to...…”
Section: Molecular Dynamics Simulations Of 2:71 Microhelix Ala Variantssupporting
confidence: 76%
See 2 more Smart Citations
“…Meaningful interpretation of MD simulations requires that each trajectory's stability be determined+ To this end, various parameters were examined to assess convergence+ The root-mean-square deviation (RMSD) from the average structure was calculated for the wild-type microhelix Ala simulation and each of the 2:71 variant simulations over a 2-ns production run time (Fig+ 5)+ Analyses of helical parameters were also examined, including local twist, base-pair inclination, and x-displacement from the global helical axis+ Appreciable fluctuations from a constant value were not observed in the RMSDs or in the helical parameters (data not shown)+ Thus, all trajectories in this study were established as reliable for interpretation+ All helices exhibited A-form geometries with the exception of local twist deviations around the G3:U70 wobble base pair+ Such geometries are consistent with prior NMR, X-ray, and MD simulation studies on the wild-type microhelix and related analogs (Ramos & Varani, 1997;Vogtherr et al+, 1998;Mueller et al+, 1999;Nagan et al+, 1999)+ Analysis of hydration indicated a water molecule to be tightly bound at the 3:70 position in every case examined here, consistent with prior experiments and simulations (Mueller et al+, 1999;Nagan et al+, 1999) for wild-type microhelix Ala + Along with structural properties, we also examined the relationship between base-pair substitution and RNA electrostatic properties+ The electrostatic potential (ESP) computed by solving the linearized PB equation is expressed as the free energy of interaction between the RNA and a unit positive charge+ The calculation is performed considering two different dielectric regions (solute and solvent) defined by the solvent-accessible surface+ This type of calculation can provide insights into how a cation, a positively charged side chain, or a protein with a positive electrostatic potential may interact with the RNA+ Such sites will also interact strongly with hydrogen-bond donating groups, including water+ PB calculations are routinely used to describe proteinsmall molecule (Ullmann et al+, 2000) and protein-DNA interactions (Misra et al+, 1994), and recently, Chin and coworkers have used PB methods to describe specific RNA electrostatics (Chin et al+, 2000)+ Van der Waals components can be further added to the electrostatic component in such a way that steric effects, derived from the actual size of atoms involved in the interaction, are also taken into account+ The sum of these two terms defines the molecular interaction potential (MIP), as originally described in the context of quantum mechanical systems by Orozco and Luque and later extended to classical systems (Orozco & Luque, 1993)+ MIP isopotential contours at Ϫ5+5 kcal/mol for various microhelices are shown in Figure 6+ All microhelices are shown from the major groove side+ The isopotential contour around the wild-type microhelix Ala indicates that there is a large region of negative interaction potential throughout the major groove, beginning at the 5:68 base pair and extending up the helix roughly to the 2:71 base pair+ Notwithstanding structural similarities between all microhelices studied, a striking difference in interaction potentials was observed with respect to...…”
Section: Molecular Dynamics Simulations Of 2:71 Microhelix Ala Variantssupporting
confidence: 76%
“…The negative potential in the major groove of RNA implies that positively charged ions or polar groups acting as hydrogen bond donors (to include water) may be expected to specifically bind within this groove+ Divalent cations have been found bound to the major groove in many RNAs (Ott et al+, 1993;Cate & Doudna, 1996;Kieft & Tinoco, 1997;Correll et al+, 1997;Le et al+, 1998;Suga et al+, 1998)+ In our simulations we have also found that monovalent sodium ions tend to bind to the major groove of wild-type microhelix Ala (nonspecifically) near the tetraloop and at the top of the acceptor stem, as both regions are solvent-or ion-accessible (data not shown)+ Whether ion interactions or direct major-groove interactions with a positive surface on AlaRS are individually or jointly critical for aminoacylation activity cannot be determined in the absence of more structural information about the enzyme-substrate complex+ A separate and interesting possibility is that the change in MIP may influence the degree to which water is bound at the G3:U70 wobble position+ It is well established, both from crystallography (Mueller et al+, 1999) and MD simulations (Nagan et al+, 1999), that in the wild-type microhelix, a water molecule is very strongly bound to this position+ The release of this water, assuming it is replaced by an enzymatic contact having a similar enthalpy of interaction, may provide an entropic driving force for enzyme-substrate binding+ To the extent that the enthalpy of interaction decreases, it may be that looser water binding reduces the entropy available to the system from release of bound water to the solvent+ CONCLUSIONS In summary, 2:71 base-pair functional groups significantly affect the electrostatics of the alanine acceptor stem+ Sequence-specific effects upon ion binding Young et al+, 1997;Auffinger & Westhof, 2000) and molecular electrostatics (Chin et al+, 2000) have been examined by others+ For example, Chin and coworkers recently noted that PB calculations of surface potentials varied with RNA sequence and that these differences might predict drug or cation binding (Chin et al+, 2000)+ Our study provides new insights into the potential similar importance of electrostatics for protein recognition of an RNA surface+ In particular, we show that there is a statistically significant correlation between the electrostatic potential in the major groove of the tRNA acceptor stem and aminoacylation with alanine+ To our knowledge, this study provides the first example demonstrating the importance of such effects for specific protein-RNA recognition+…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[19,20], (2) the differences between RNA and DNA structures of similar sequence [19][20][21] or (3) the effects associated with the introduction of natural [22,23] and non-natural modified nucleotides [24,25]. In order to generate larger systems, model built fragments can also be assembled with motifs derived from X-ray or NMR structures [26].…”
Section: Choosing the Starting Structurementioning
confidence: 99%
“…OR(n ϩ 1) hydrogen-bond pattern observed in RNA. 20,21,29,30 Other methods rely on the time spent by a water molecule in a 5 Å sphere around a given solute atom 31 or use coordination correlation function approaches. 14,32,33 Worth mentioning is that none of the above methods can give statistically exact values for the residence times of the most strongly bound water molecules, since the length of a MD simulation should be many times longer than the longest calculated residence times.…”
Section: Dynamics: Determination Of Residence Timesmentioning
confidence: 99%